2021
DOI: 10.1080/0886022x.2021.1889600
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological assessment of radial artery calcification in patients with end-stage kidney disease

Abstract: Background A comprehensive understanding of vascular calcification pathology is significant for the development of cardiovascular disease therapy in high-risk populations. This cross-sectional study aimed to evaluate the prevalence and characteristics of radial artery calcification (RAC) and to identify the factors that are associated with RAC in end-stage kidney disease (ESKD). Methods Detailed medical histories of 180 patients with ESKD were recorded. Fragments of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…In this study, the analysis was conducted by R (R Foundation for Statistical Computing, Vienna, Austria, Version 4.2.2) on random forest package (Version 4. [6][7][8][9][10][11][12][13][14]. The parameters for random forest were as follows: The Gini index was set as an impurity function; number of decision trees (ntree) = 500, mtry = 9 (RF model)/7 in variablerestricted RF (vrRF) model; and set as at default settings for all the other parameters (see Data S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the analysis was conducted by R (R Foundation for Statistical Computing, Vienna, Austria, Version 4.2.2) on random forest package (Version 4. [6][7][8][9][10][11][12][13][14]. The parameters for random forest were as follows: The Gini index was set as an impurity function; number of decision trees (ntree) = 500, mtry = 9 (RF model)/7 in variablerestricted RF (vrRF) model; and set as at default settings for all the other parameters (see Data S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…12 Histology examination of radial arteries by Chen et al found that 21% of patients with hemodialysis had arteries calcifications. 13 Niu et al identified radial artery calcifications in 24.7% of peritoneal dialysis patients. 14 Moreover, Wang et al suggested that multiple risk factors could contribute to the radial artery calcification in hemodialysis patients, including deposition of osteopontin, deficient expression of alpha-smooth muscle actin, and metabolic disorder of phosphorus and calcium.…”
mentioning
confidence: 99%
“…Mizuiri et al (2021) showed that many factors significantly affect the probability of CAC in patients undergoing hemodialysis treatment, such as smoking, hs-CRP, diabetes, phosphate levels, gender, time on dialysis, age and blood calcium levels. Chen, Zhou & Yang (2021) studied the factors that affect radial artery calcification in patients with end-stage renal disease and found that calcium levels, HbA1c levels, duration of diabetes and duration of dialysis treatment are positively correlated with the degree of radial artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike atherosclerosis, medial calcification is similar to osteogenesis and is mainly regulated by vascular smooth muscle cells (VSMCs) ( Ottolini & Sonkusare, 2021 ). One of the main mechanisms of VC is the accelerated rate of VSMC synthesis and senescence, decreased contractile protein expression, and gradual transdifferentiation into an osteoblastic/chondrocyte phenotype that releases matrix vesicles ( Chen, Zhou & Yang, 2021 ). When high phosphate levels are present, differentiation of VSMCs into a bone/chondrogenic phenotype can occur ( Voelkl et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium phosphate salts start to accumulate in vascular wall over time in ESRD patients. Furthermore, changes occur in vascular smooth muscle cells due to impaired mineral metabolism, which leads to arterial calcification[21]. This process causes a disruption in vascular structure as the duration of ESRD increases.…”
mentioning
confidence: 99%